Authority, Academic Discourse and Ideology in the ESL Writing Class: An ESL teacherâ€™s experience - Kanakri, Aseel (Widya Mandala Catholic University Surabaya, 2015)
This paper describes an ESL teachersâ€™ perspective on teaching ESL writing to advanced second language learners reflecting on her experience as an ESL teachers drawing on the studentsâ€™ responses to survey questions. It shows that writing in English as a Second language has political, cultural, and historical aspects since the â€œnature and functions of discourse, audience, and persuasive appeals often differ across linguistic, cultural, and educational contextsâ€ In addition, acquiring the discourse proprieties is challenging because they represent culturally bound, conventionalized, and abstract characteristics of academic prose that are frequently absent in written discourse in rhetorical traditions other than the English dominant educational environments. ESL teachers should get the awareness of the needs and challenges that the face and understand the linguistic, cultural, and educational background they are coming from in order to help them overcome these challenges which also should dictate the instructional pedagogies, curriculum and assessment. Keywords: academic discourse, ESL writing, teacherâ€™s perspective, ideology